Development and application of a PBPK modeling strategy to support antimalarial drug development - Nada Abla; Eleanor Howgate; Karen Rowland‐Yeo; Maurice Dickins; Mackenzie C. Bergagnini‐Kolev; Kuan‐Fu Chen; Savannah McFeely; Jennifer J. Bonner; Laura G. A. Santos; Nathalie Gobeau; Howard Burt; Zoe Barter; et al. (Wiley, 2023)
Abstract As part of a collaboration between Medicines for Malaria Venture (MMV), Certara UK and Monash University, physiologically‐based pharmacokinetic (PBPK) models were developed for 20 antimalarials, using data obtained from standardized in vitro assays and clinical studies within the literature. The models have been applied within antimalarial drug development at MMV for more than 5 years. During this time, a strategy for their impactful use has evolved. All models are described in the supplementary material and are available to researchers. Case studies are also presented, demonstrating real‐world development and clinical applications, including the assessment of the drug-drug interaction liability between combination partners or with co‐administered drugs. This work emphasizes the benefit of PBPK modeling for antimalarial drug development and decision making, and presents a strategy to integrate it into the research and development process. It also provides a repository of shared information to benefit the global health research community.